Challenges and research directions in autonomic communications. (5th December 2006) - Curran, Kevin; Mulvenna, Maurice; Nugent, Chris; Galis, Alex
The increasing amount of traditional network services may still not fulfil the requirements of ever-demanding applications and must therefore be enriched by some form of increased intelligence in the network. This is where the promise of autonomous systems comes into play. Autonomous systems are capable of performing activities by taking into account the local environment and adapting to it. No planning is required; therefore autonomous systems must optimise the use of the resources at hand. This paper clearly identifies the need for autonomous systems in networking research, anticipated architectures, characteristics and properties, the path of evolution from traditional network elements and the future of such systems.